1994
DOI: 10.1139/v94-277
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and crystal structure of a mixed-phosphine ligand Tc(II) complex, Tc(PMe2Ph)2(DMPE)Cl2

Abstract: The reaction of Tc(PMe,Ph),Cl, with an excess of bis(dimethy1phosphino)ethane (DMPE) in ethanol solution produced a yellow compound, which was identified by X-ray diffraction methods as a mixed-ligand Tc(I1) complex, TC(?M~,P~)~(DMPE)C~,.The compound crystallizes in the P2,lc space group with a = 12.899(6), b = 13.142(8), c = 19.088(9) A, P = 121.13(3)", V = 2770(2) A~, Z = 4, R = 0.061, and R,,, = 0.05 1. The geometry around the Tc atom is octahedral with the chloro ligands trnr~s to each other, while the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
4
0
2
Order By: Relevance
“…The trans angles P−Tc−P are 168.17(3) and 170.84(3)°, while the Cl−Tc−Cl angle is 176.97(3)°. The Tc−Cl bond distances are 2.325(1) and 2.330(1) Å, close to the average value of 2.335 Å reported for 11 published similar Tc(III) structures . The Tc−P bonds vary between 2.490(1) and 2.536(1) Å.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The trans angles P−Tc−P are 168.17(3) and 170.84(3)°, while the Cl−Tc−Cl angle is 176.97(3)°. The Tc−Cl bond distances are 2.325(1) and 2.330(1) Å, close to the average value of 2.335 Å reported for 11 published similar Tc(III) structures . The Tc−P bonds vary between 2.490(1) and 2.536(1) Å.…”
Section: Resultssupporting
confidence: 79%
“…These values are slightly long for Tc(III) compounds. In a short review, the average value found for Tc(III)−P bond distances for monodentate phosphines located in trans positions to other phosphines is 2.478 Å (based on nine structures) . The slightly longer value observed in crystal I (average 2.512(1) Å) probably results from the strain caused by the presence of four relatively bulky phosphine ligands.…”
Section: Resultsmentioning
confidence: 97%
“…38( 2) C( 14) -874 (12) 2432( 9) 4511( 10) 54(2) C( 46) 6104( 11) 930( 8) 769( 10) 41(2) C (15) -1507 (12) 1867( 8) 4129( 10) 46(2) C( 51) 5554( 10) 363( 7) 2673( 8) 25(2) C( 16) -1054 (12) 1437( 8) 3530( 10) 41(2) C( 52) 5487( 11)…”
Section: Resultsunclassified
“…-882( 9) 2629( 11) 55(2) C( 22) -628 (12) -286( 8) 2051( 13) 58(2) C954) 6682 (13) -807( 9) 3565( 11) 59(2) C( 23) -879 (14) -979 (12) 2317( 16) 92(2) C( 55) 6747 (12) -176( 8) 3993( 10) 49(2) C(24) -584 (15) -1196( 9) 3149( 16) 89(2) C( 56) 6207( 11) 388( 8) 3556( 10) 42(2) C( 25) 63 (15) -789( 9) 3821( 14) 75( 2)…”
Section: Resultsunclassified
“…These values are not very precise for crystal I (even if the estimated standard deviations are acceptable), because of the important disorder of the ethyl groups on P(3), but similar angles were observed in other technetium-phosphine complexes. [22][23][24][25][26][27] The C-C-C angles of the PPr 3 compound are slightly flattened averaging 113.9(7)°.…”
Section: Resultsmentioning
confidence: 99%